The Rise of the Accounting Profession: To Responsibility and Authority. - Barr, Andrew; Sterling, Robert R. (The Accounting Review, 1971)
Reviews the book "The Rise of the Accounting Profession: To Responsibility and Authority: 1937 to 1969," vol. 2, by John L. Carey.